Analysis of Leadership Style and Salary on Employee Performance - Languyu, Nolchi Yudian (Journal of Management, 2024)
The goals and direction of the organization, as well as the obstacles a leader faces, are greatly influenced by employee performance in the workplace. It will assist a business in reaching its objectives if it is bolstered by competitive pay, strong leadership, and motivated staff. When taken as a whole, these three elements influence worker performance, which eventually results in organizational success. The purpose of this study is to investigate how an employee's pay, job motivation, and leadership style relate to their performance: a case study at CV. Rays of health. CV is the subject of this study. Good Sinar Using all CV employees as the population, this study used quantitative methodologies. 46 healthy Sinar were selected using a saturation sample method. The Smart-PLS version 4.0 device is employed in the SEM method of analysis. The outer model test, the mediation test, and the hypothesis test are the tests